Modern world history for Edexcel specification A - Kelly, Nigel (Heinemann, 2001)
This student book is a foundation edition of the syllabus specific text for GCSE "Modern World History" for Edexcel. This text provides a simplified version of the core textbook and is targeting students expecting to gain C to G grades.